Weak Essential Fuzzy Submodules Of Fuzzy Modules - K. Marhon, Hassan; Y. Khalaf, Hatam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Throughout this paper, we introduce the notion of weak essential F-submodules of F-modules as a generalization of  weak essential submodules. Also we study the homomorphic image and inverse image of weak essential F-submodules.